Struggling to Speak: A Case Study of Students’ Barriers in English Public Speaking - Supriyanto, Supriyanto; Ilham , Ilham; Edi, Edi; Bafadal, Moh. Fauzi (Journal of English Education and Linguistics, 2025)
This study investigates the challenges students face in developing their English public speaking skills and identifies the factors that influence their performance. Using a descriptive qualitative approach and a case study design, data were collected through semi-structured interviews and classroom observations involving third-semester students of the English Education Study Program. The data were analyzed using an inductive approach through Miles and Huberman’s interactive model. The findings reveal four major categories of challenges. Preparation-related difficulties emerged as students often lacked adequate rehearsal, resulting in disorganized delivery and low confidence. Linguistic barriers, including limited vocabulary, grammatical inaccuracy, pronunciation problems, and disrupted fluency, further affected their ability to express ideas clearly. Psychological factors such as anxiety, shyness, and fear of negative evaluation also played a crucial role in hindering performance. Additionally, environmental and social constraints, such as limited speaking opportunities and insufficient support from peers and lecturers, restricted students’ development of speaking competence. Overall, the study highlights that students’ public speaking challenges are multidimensional. It emphasizes the need for comprehensive instructional support that integrates preparation strategies, linguistic development, confidence-building techniques, and increased speaking practice.